Konsep Perlindungan Pengetahuan Tradisional Berdasarkan Asas Keadilan Melalui Sui Generis Intellectual Property System - Imas Rosidawati (Fakultas Hukum Universitas Islam Indonesia, 2013)
This research aims to analyze and observe the answer for several issues: first, finding out the legal protection for Intellectual Property Rights in traditional science in consideration to the absence of a particular regulation in Indonesia laws; second, to find out a concept of equitable management of the traditional science in order to support the economic development in Indonesia. The approach used in this research refers to both judicial-normative method and judicial-comparative method. The result of the research then reveals the following conclusions: first, the protection for Intellectual Property Rights towards traditional science using the regulations of Intellectual Property Rights, in fact, cannot give a total protection. In essence, the protection of Intellectual Property Rights is exclusive, monopolistic, andindividualistic making it to be privat domain. This is much different from the nature of traditional science more focused on collectivism. Second, the precise concept of traditional science management is by regulating the Sui Generis law that is by making prior art as a protection by accommodating the equitable concept of “benefit sharing”. The existing regulation of Intellectual Property Rights after Indonesia ratified TRIPs cannot give any justice for the protection towards traditional science for the existence of misappropriation.